Membentuk Peserta Didik Mengembangkan Sikap Inklusif dan Toleran Berdasarkan Nilai Nilai Iman Kristiani - Gimson Sitinjak; Menderita Lilis Helena Purba; Hisardo Sitorus (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
The goal of Christian education is not only to increase students' knowledge but also to shape character that reflects the values ​​of faith in Christ. In the context of a diverse society, an inclusive and tolerant attitude towards differences is crucial for students. This paper aims to illustrate how students can be shaped to develop an inclusive and tolerant attitude based on the values ​​of the Christian faith. Through Christian Religious Education (PAK) learning that emphasizes love, respect for one another, justice, and peace, students are encouraged to recognize that every human being is created in the image and likeness of God. An inclusive and tolerant attitude can develop when students understand that differences are part of God's plan and implement this in their interactions with others. Therefore, Christian education plays a crucial role in instilling the value of Christ's love so that students can live peacefully together, appreciate differences, and become role models in a diverse society.